Application of propidium monoazide quantitative PCR to discriminate of infectious African swine fever viruses - Li, Yang; Wang, Zewei; Qing, Jie; Hu, Dajun; Vo, Hong Trang; Thi, Kim Thanh; Wang, Xinglong; Li, Xiaowen (Frontiers in Microbiology, 2024)
The detection of African swine fever virus (ASFV) is commonly performed using quantitative real-time PCR (qPCR), a widely used virological method known for its high sensitivity and specificity. However, qPCR has a limitation in distinguishing between infectious and inactivated virus, which can lead to an overestimation of viral targets.To provide insights into ASFV infectivity, we evaluated the suitability of PMAxx, an improved version of propidium monoazide (PMA), as a means to differentiate between infectious and non-infectious ASFV. Pre-treatment with 50 μM PMAxx for 15 minutes significantly reduced the qPCR signal of ASFV in the live vaccine. Additionally, thermal treatment at 85°C for 5 minutes effectively inactivated the live ASFV in the vaccine. Based on a standard curve, the sensitivity of the PMAxx-qPCR assay was estimated to be approximately 10 copies/μL. Furthermore, we observed a strong agreement between the results obtained from PMAxx-qPCR and pig challenge experiments. Moreover, we utilized the PMAxx-qPCR assay to investigate the persistence of ASFV, revealing a close relationship between viral persistence and factors such as temperature and type of piggery materials.The findings of this study suggest that pre-treating viruses with PMAxx prior to qPCR is a reliable method for distinguishing between infectious and non-infectious ASFV. Thus, integrating of PMAxx-qPCR into routine diagnostic protocols holds potential for improving the interpretation of positive ASFV results obtained through qPCR.